Online reviews credibility and website quality: implications on travellers’ decision making - Lopes, Romeu Mendes da Silva (2015)
The online travel sales represent a considerable market share and a continued growth is predicted in the coming years. With the evolution of information and communication technologies, the online platforms emerge as important information sources for an increasingly informed and demanding tourist. Actually, the number of tourists who prefer and trust in websites with amateur reviews is growing. Giving the emergence of this social interaction process nowadays part of the power of marketing lies in consumers. Social media and the new digital form of word-of-mouth (eWOM) are receiving a significant attention by researchers, especially in the context of the tourism sector. However, there is a need to further explore the subject, trying to understand how the online reviews influence the choice of a given hotel, and find the best way to use social media to interact with actual and potential customers. On the other hand, website quality and customer satisfaction emerge as critical business concerns, especially in an e-commerce perspective, due to the low percentage of website visitors that purchase from it. Accordingly, there is a lack of research on the assessment and satisfaction degree of tourists regarding websites targeted for booking accommodation online. This research aims to increase knowledge concerning these subjects. The study develops the ReWebility framework that explores the website’s quality and the credibility of online reviews, and their influence on tourist’s decision-making process, especially tourist’s loyalty to those websites. In this research we follow a quantitative approach, resorting to an online questionnaire. The sample consists of 351 internet users who have already booked accommodation through online platforms. Initially we proceeded to a descriptive analysis using SPSS software, followed by a confirmatory factor analysis and a structural equation model (SEM). The results confirm that tourists read online reviews before choosing a hotel, and consider them as trusted, credible and accurate. The proposed model suggests a chain between online reviews credibility, company reputation, e-satisfaction and e-loyalty, which might be the basis for further investigations related to consumer behaviour in online settings. The perceived value of the hotel reviewed and booked is the most influential determinant for a satisfactory online booking experience. In order to induce tourists to book online the website should ensure the best price, but not necessary the lowest one. At the end we will discuss the theoretical contributions and the practical implications, some suggestions, and future research lines.